Rivaroxaban dosing in patients with atrial fibrillation: results from the RIVER registry – is dosing according to renal function appropriate?. (14th October 2021) - Camm, A.J; Virdone, S; Fox, K.A.A; Pieper, K.S; Beyer-Westendorf, J; Le Heuzey, J.-Y; Haas, S; Kayani, G; Gersh, B.J; Turpie, A.G.G; Kakkar, A.K; ,
Abstract: Introduction: Rivaroxaban is recommended as an option for anticoagulation in patients with nonvalvular atrial fibrillation (AF) with one or more risk factors for stroke. The approved/recommended rivaroxaban dose for stroke prevention in patients with atrial fibrillation (AF) is solely based on renal function: 20 mg once daily (od) for patients with a creatinine clearance [CrCl] ≥50 ml/min and 15 mg od in patients with CrCl 15–49 mL/min). Purpose: To assess the patterns of rivaroxaban prescription as per the creatinine clearances levels and to assess the impact of the rivaroxaban dosing on the rate of events at 2-year follow-up in patients with AF. Methods: RIVaroxaban Evaluation in Real Life setting (RIVER) is a prospective international registry of patients with newly diagnosed non-valvular AF treated with rivaroxaban for the prevention of thromboembolic stroke and at least one investigator-determined risk factor for stroke. Adjusted hazard ratios (HRs) were obtained through Cox proportional-hazard model. Results: Among 3402 patients with normal renal function (CrCl ≥50 mL/min), 82.1% were prescribed the recommended rivaroxaban dose of 20 mg (od) at baseline. Among 524 patients with moderate or severe renal impairment (CrCl 15–50 mL/min), 55.3% patients received rivaroxaban 15 mg (od), 39.9% received 20 mg (od) and 4.2% 10 mg (od). Non-recommended dosing was rare in patients younger than 70 (13.5%) but more frequent in older patients (28.8%). Non-recommended low dosing was more frequent in Asians (38.9%), compared to non-Asian patients (13.8%). Regarding clinical outcomes, adjusted hazards ratios (HR, presented with 95% confidence intervals) showed that the non-recommended low dosing (<20 mg od) was associated with higher risk of non-cardiovascular mortality (HR 2.09 (1.16–3.77)) in patients with normal renal function. The non-recommended high dosing (>15 mg od) was associated with lower risk of all-cause mortality (HR 0.63 (0.42–0.93)) and cardiovascular mortality (HR 0.32 (0.13–0.77)) and higher risk of major bleeding (HR 2.86 (1.49–5.50)) in patients with moderate to severe renal impairment (figure 1 and 2). Conclusion: In patients with normal renal function, non-recommended low dose rivaroxaban was associated with increased cardiovascular mortality without reducing the risk of major bleeding compared to recommended dosing. In patients with CrCl <50 ml/min, non-recommended high dose rivaroxaban was associated with reduced cardiovascular mortality but at the cost of increased major bleeding. These observational data largely support the reduction of rivaroxaban dosing according to renal function but educational strategies are needed to ensure that rivaroxaban is used appropriately. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This work was supported by an unrestricted research grant from Bayer AG, Berlin, Germany, to TRI, London, UK, which sponsors the RIVER registry. This work is supported by KANTOR CHARITABLE FOUNDATION for the Kantor-Kakkar Global Centre for Thrombosis Science.